The Impact of Failure Types in Construction Production Systems on Economic Risk Assessments in the Bidding Phase. (13th November 2018) - Mirkovic, Milan
Abstract : The aim of the paper is to research and analyze the impact of the type of failure on economic risks in the bidding phase, as the most important part in the management of construction projects. The survey included the impact of risk on the process of determining unit prices from the perspective of a potential contractor. Also, the failure rate and repair rate of the 34 machines from the machine park of the company for road construction were researched. On the basis of obtained parameters and depreciation periods, the operational availability of components of construction production systems was determined. The proposed methodology for estimating impact of the availability function is a modified method of the frequency balancing. It has been tested on a concrete project from the practice in the process of harmonizing construction norms of time that preceded the final adoption of the unit prices. Differences in prices are results of the system failure of construction machinery and plants and have justified a hypothesis of obtaining more realistic costs that can occur in the projects.